Development of e-LKPD Using Flip PDF Professional on Coordination System Material for F Phase Students - Rachmat Meydi; Afreni Hamidah; Raissa Mataniari (Jurnal Penelitian Pendidikan IPA, 2024)
Coordination system is a complex material due to its many sub-discussions. Teachers’ limited time to discuss questions with students causes students to have difficulties in understanding the material. To overcome this problem, e-LKPD which can streamline learning time and act as a solution to students' difficulties related to the lack of time to do practice questions is required. This research aims to develop an e-LKPD using Flip PDF Professional on coordination system material and analyze the feasibility of the developed product. This research uses the ADDIE development model which consists of Analyze, Design, Develop, Implement and Evaluation. The results of the research show that the e-LKPD developed obtained a percentage of 93.30% in the "very feasible" category. In the media validation stage, a percentage value of 81.67% was obtained in the "very feasible" category. Biology teachers' perceptions regarding the quality of the developed product obtained a percentage of 96.70% in the "very good" category. Small group trials with students obtained a percentage of 86.70% in the "very good" category and large group trials obtained a percentage of 89.60% in the "very good" category. Therefore, it can be concluded that the developed product is feasible and practical for students to use.